Linguistic examination of social networks under conditions of hybrid challenges to Ukraine's national security - Kompantseva, Larysa (Current issues of Ukrainian linguistics: theory and practice, 2020)
The article analyses the applied aspects of linguistic examination of social networks under conditions of hybrid threats to the national security of Ukraine. It is argued that the intensification of intercultural communications, the formation of a single geopolitical space, the activation of destructive influences on the behaviour of social network visitors have led to an increase in discursive situations that a linguist can evaluate as an expert. For these reasons, there is an urgent need to separate and legislate linguistic examination of social networks, i.e. linguistic analysis of social network discourses using an integrated approach, the results of which can be completed as an advisory opinion or forecast concerning the impact of virtual communication on socio-political activity in the real world. This type of examination has got importance under conditions of hybrid aggression of the Russian Federation, which is mainly aimed to reshape the system of values and behaviour in target audiences, though it is of a consciental nature. The expert approach is the most relevant for identifying social cyberattacks, i.e. anonymous manipulative influences on social network visitors to create chaos, panic, and mass unrest. This identification should consider the following discursive characteristics of social networks: the creation of attractive content, its coordinated distribution through public and private channels, the use of social bots, the horizontal broadcasting of narratives. As an example, it is proposed the linguistic examination of the Russian propaganda fake “anti-Semitism in Ukraine”, which purpose is to ignite ethnic agitation. Therefore, active integration of academic community into the analysis of modern threats and counteraction to them, creation of a pool of professional experts, legislative regulation of the status of linguistic examination of social networks are on the agenda.
Keywords: hybrid threats, linguistic examination of social networks, narrative, social cyber-attacks, strategic communications, suggestive technologies of influence, fake.